2012
DOI: 10.2967/jnumed.111.102277
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Optimal Time Point for the Measurement of Extrastriatal Serotonin Transporter Binding with 123I-FP-CIT SPECT in Healthy, Male Subjects

Abstract: 123 I-N-v-fluoropropyl-2b-carboxymethoxy-3b-(4-iodophenyl) nortropane ( 123 I-FP-CIT) is commonly used to assess the dopamine transporter in the striatum. However, recent studies suggest that this tracer may be used also to assess binding to monoamine transporters in the midbrain or diencephalon, which may reflect predominantly serotonin transporter (SERT) binding. However, it is still unclear at what time point after injection SPECT should be performed for optimal assessment of SERT with 123 I-FP-CIT. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 19 publications
4
31
1
Order By: Relevance
“…6,7 Therefore, given that our images were acquired at 4 hours, it may not reflect at the maximum uptake value in the MB.…”
Section: Discussionmentioning
confidence: 98%
“…6,7 Therefore, given that our images were acquired at 4 hours, it may not reflect at the maximum uptake value in the MB.…”
Section: Discussionmentioning
confidence: 98%
“…The activity in the separate ROIs was combined to reflect average activity in the caudate nucleus (left + right), putamen (left + right) and whole striatum bilaterally. The cerebellum was used as reference region by positioning an ROI, as described previously [31]. For the [ 123 I]IBZM images, fixed ROIs were positioned for the striatum, as described previously [32].…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, we combined conventional magnetic resonance imaging (MRI) for anatomical reference with SPECT imaging of the SERT with [ 123 I]FP-CIT using a brain-dedicated system [22,23]. This radiotracer is approved to visualize and quantify dopamine transporters as early as 3 h after injection [24], but more recent studies showed its capacity to assess specific binding to extrastriatal SERT as well.…”
Section: Introductionmentioning
confidence: 99%